Answer :

Put (x^{2} – x) = a

⟹ a^{2} – 8a + 12

⟹ a^{2} – 2a – 6a + 12

⟹ a (a-2) – 6(a-2)

⟹ (a-6) × (a-2)

⟹ but a = (x^{2} – x)

⟹ ((x^{2} – x)-6) × ((x^{2} – x) – 2

⟹ (x^{2} – x -6) × (x^{2} – x -2)

⟹ (x^{2} –3x + 2x – 6) × (x^{2} – 2x + x -2)

⟹ (x (x-3) + 2(x – 3)) × (x(x-2) + 1(x-2))

⟹ (x + 2)(x-3)(x-2)(x+1)

Therefore, the factorized form = (x + 2)(x-3)(x-2)(x+1)

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Factorize the folMHB - Math Part-I

Factorize the folMHB - Math Part-I

Factorize the folMHB - Math Part-I

Factorize the folMHB - Math Part-I

Find the factors MHB - Math Part-I

Find the factors MHB - Math Part-I

Find the factors MHB - Math Part-I

Factorize the folMHB - Math Part-I

Factorize the folMHB - Math Part-I

Factorize the folMHB - Math Part-I